A liquid crystal cell with double-side protrusion electrodes for fast response and low-voltage operation. Issue 3 (19th February 2016) - Choi, Tae-Hoon; Park, Young-Jin; Kim, Jung-Wook; Yoon, Tae-Hoon
ABSTRACT: We propose a homogeneously aligned liquid crystal (LC) cell with double-side protrusion electrodes for fast response and low-voltage operation. In the proposed device, both the bottom and top substrates have pixel electrodes to generate the fringe electric field. Because the penetration depth of the electric field is increased owing to the protrusion electrodes, the operating voltage is very low and the turn-on time is dramatically reduced compared with the conventional in-plane switching (IPS) mode. Moreover, LC molecules anchored strongly to the penetrated protrusion electrodes on both substrates exert a strong restoring force, resulting in a fast turn-off time. We found that the total response time of the LC cell with the proposed structure is three times faster than that of the conventional IPS mode. GRAPHICAL ABSTRACT: